Performance of grid-connected photovoltaic systems in Northern and Southern Hemispheres under equatorial climate - Abdul Rahim, Yang Ilya Akila; Zainuddin, Hedzlin; Setiawan, Eko Adhi; Madsuha, Alfian Ferdiansyah; Hussin, Mohamad Zhafran; Sulaiman, Shahril Irwan; Ibrahim, Siti Nor Nadhirah (Institute of Advanced Engineering and Science, 2024)
This work studied the actual and simulated technical performance between two grid-connected photovoltaic (GCPV) systems representing opposite latitudes. The system with a capacity of 5.4 kWp installed in Kelantan, Malaysia represents the northern equator, and the 183.6 kWp system installed in Cikarang, Indonesia, denotes the southern equator. The performance was simulated using PVsyst software, which included the energy output (E_outt), reference yield (Y_r), final yield 〖(Y〗_f), performance ratio (PR), and capacity factor (CF). The mean bias error (MBE) between the actual and simulated technical performance were as follows; for system A, the yearly MBE for the E_out, Y_r, Y_f, PR, and CF were -0.4%, 17.1%, -1.4%, -15.8%, and 1.4%, respectively, and for system B, the E_out, Y_r, 〖 Y〗_f, PR, and CF values were 9.80%, 18.3%, 10.0%, -7.2%, and 10.0% respectively. The results have proven that PVsyst has successfully simulated the yearly E_out, 〖 Y〗_f and CF for both systems including PR, for system B, with MBE less than 10%. However, it is noteworthy to highlight that PVsyst significantly overestimated the Y_r of both systems up to 18.3% and conversely underestimated the PR for system A by 15.8%, which highly likely caused by the Meteonorm imported weather data.